2014
DOI: 10.1212/wnl.0000000000000310
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory fitness and cognitive function in middle age

Abstract: Objective: To investigate whether greater cardiorespiratory fitness (CRF) is associated with better cognitive function 25 years later. Methods:We studied 2,747 participants in the community-based Coronary Artery Risk Development in Young Adults Study of black and white men and women aged 18 to 30 years at recruitment in [1985][1986] Results: Per minute of baseline CRF, the RAVLT was 0.12 words recalled higher (standard error[SE] 5 0.03, p , 0.0001), the DSST was 0.92 digits higher (SE 5 0.13, p , 0.0001), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 41 publications
4
65
0
3
Order By: Relevance
“…Consistent with previous research, this study found that the potential beneficial effects of regular physical activity participation and a healthy body weight on the vascular and cognitive health of young adults have been previously highlighted (Zhu et al, 2014;Zhu et al, 2013). Evidence suggests that physical inactivity, pooper cardiorespiratory fitness, or obesity increases CRP levels and impairs cognitive dysfunction.…”
Section: Crp and Health Indicessupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with previous research, this study found that the potential beneficial effects of regular physical activity participation and a healthy body weight on the vascular and cognitive health of young adults have been previously highlighted (Zhu et al, 2014;Zhu et al, 2013). Evidence suggests that physical inactivity, pooper cardiorespiratory fitness, or obesity increases CRP levels and impairs cognitive dysfunction.…”
Section: Crp and Health Indicessupporting
confidence: 89%
“…Although the relationship between cardiorespiratory fitness and cognitive function have been observed in childhood (Hillman, Author, & Buck, 2005), middle adulthood (Zhu et al, 2014), and late adulthood (Hayes, Forman, & Verfaellie, 2014), the association of cardiorespiratory fitness and CRP with cognitive function in young adults is less clear. Young adult CRP-cognitive function research has been inhibited by small samples, as risk is not as prevalent in this age group (Author et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, polyphenols and resveratrol mediate multiple of the previously described pathways such as SIRTs, AMPK and mTOR (Lam et al 2013). In longitudinal clinical interventions conducted in humans, increased consumption of polyphenol-rich and Mediterranean-type food items such as extra-virgin olive oil and nuts has been associated with markers of healthy aging such as improvement of cardiovascular risk factors and cognition (Valls-Pedret et al 2012;Martinez-Lapiscina et al 2013;Zhu et al 2014;Houston et al 2015). Moreover, a resveratrol supplementation study in healthy aged individuals improved brain functional connectivity, which correlated with improved glucose metabolism and memory (Witte et al 2014).…”
Section: Calorie Restriction Mimetics: the Case Of Polyphenolsmentioning
confidence: 99%
“…[20][21][22][23][24][25][26] In addition, we previously found that higher CRF was related to better cognitive function in participants of the CARDIA Study. 34 Better cognitive function has been observed to relate to white matter integrity in several other large population studies of middle-aged and elderly individuals. [11][12][13][14] Although these associations of CRF with cognitive function and of cognitive function with white matter characteristics do not necessarily mean that brain MRI parameters would be better in those with higher or improved treadmill duration, the evidence presented here is consistent with the hypothesis that brain volume and white matter integrity might respond to improved CRF.…”
mentioning
confidence: 94%